EXAMINING THE LINK BETWEEN ENVIRONMENTAL TAX VOLATILITY AND THE SHIFT TO RENEWABLE ENERGY IN UKRAINE - Yeboah , Benjamin; Addo-Paintsil , Samuel; Baffoe , Mark Yaw; Antwi , Eric (International Journal of Accounting & Finance Review, 2025)
Environmental taxes are increasingly used as fiscal instruments to internalize environmental externalities and finance renewable energy investments. Environmental taxes are increasingly utilized as fiscal instruments to internalize environmental externalities and finance renewable energy investments. This study examines the nonlinear, regime-dependent relationship between environmental tax volatility and the renewable energy transition in Ukraine, aiming to identify stable tax regimes that effectively support renewable energy development. The study employs annual time-series data from the World Development Indicators covering the period 1980-2023. Preliminary analyses include descriptive statistics, unit root tests (ADF and PP), OLS estimation, and non-linearity diagnostics (BDS and CUSUM tests). Ordinary Least Squares results indicate that a 1% increase in environmental tax revenue increases renewable energy transition by 0.8329% (p < 0.01). Markov switching results identify two distinct regimes. Regime 2 records a higher coefficient (0.7812) and stronger persistence (P22 = 0.970) compared to Regime 1 (0.7016; P11 = 0.909). Regime 2 demonstrates lower volatility, higher mean values (0.9337), and a longer duration of approximately 33 years, indicating a stable and sustained environmental tax regime that effectively supports renewable energy transition. Maintaining stable, consistent environmental tax regimes should be the top priority for policymakers to ensure stable, consistent funding for renewable energy investments, build greater public trust, and accelerate the achievement of SDG 7 in Ukraine. JEL Classification Codes: H2, Q2, Q4.